Interuncal distance: marker of aging and Alzheimer disease. - Howieson, J; Kaye, J A; Holm, L; Howieson, D (American Journal of Neuroradiology, 1993)
PURPOSE To evaluate the utility of a recently reported simple measure of brain atrophy on MR imaging, the interuncal distance (IUD).METHODS Measurements of the IUD were made over a 12-month interval in 10 patients with probable early Alzheimer disease and in a comparison group of age-matched healthy control subjects. The measurements were made in both the transaxial and coronal planes.RESULTS Significant group differences for the coronal measurement of IUD were found in both the absolute value of the measurement and the IUD corrected for head size. There was overlap in IUD between the disease and the control groups. These differences were not found for the transaxial IUD. Significant positive correlations of the IUD with Mini-Mental State Examination score and Clinical Dementia Rating Scale stage were observed. Over the age range tested, age was not significantly correlated with IUD in the sample.CONCLUSIONS The interuncal distance (IUD) is not a useful screening measurement for Alzheimer disease.